CHEMICAL ECOLOGY OF SHALLOW WATER OCTOCORALS. OCCURRENCE OF CEMBRANOLIDES IN PSEUDOPLEXAURA AND EUNICEA - Ciereszko, Leon S. (Marine Research in Indonesia, 1977)
Gorgonians of the genus Pseudoplexaura, from a variety of geographical locations, yield crassin acetate as the major cembranolide. The cembranolides found in Eunicea collected at different locations vary. Eunicin is found in Eunicea mammosa from Bimini, and from a number of other locations. Its position isomer Jeunicin, has been found in the Eunicea from Jamaica. Eunicea from Curacao yields an epimer ot eunicin, Cueunicin, while that from Puerto Rico yields Eupalmerin acetate, and Peunicin occurs in Eunicea collected off Panama. The cembranolides are toxic to various aquatic organisms. They inhibit ciliary action in the ciliate Tetrahymena pyriformis, and in the larvae of the nudibranch Phestilla sibogae.